Actividad antimicrobiana, in vitro, del extracto etanólico de camu camu (Myrciaria dubia) contra microorganismos bucales - Pardo Aldave, Karina (2019)
Objective: To evaluate the antimicrobial activity, through the agar diffusion method with wells, of camu camu (CC) against oral microorganisms. Methods: Strains of S. aureus, S. mutans, C. albicans and P. gingivalis were inoculated in Petri dishes. Ethanolic extracts (EEs) of peel, pulp and CC seed and controls (0.12% chlorhexidine, oral antiseptic, 70° alcohol and distilled water) were loaded into 6 mm diameter wells. All plates were incubated for 24-48 h and 11 days (P. gingivalis) at 35°C and the antimicrobial activity was determined by the formation of a zone of microbial growth inhibition (ZMGI), around the wells and measured by a Vernier caliper, by a researcher, calibrated interexaminer. The average of the different ZMGI areas (mm) was determined. The experiment was executed between 3 and 14 replicas. Descriptive and inferential statistics were applied (p<0.05). Results: Seed EEs inhibited the four microorganisms. For each microorganism, significant differentiation was observed in the antimicrobial activity according to experimental group (p=0.0000) and between pairs of groups (p<0.001). Conclusion:The three parts of CC exerted different values of antimicrobial activity against oral microorganisms, being similar or superior to oral antiseptics.